HUBUNGAN MANAJEMEN KONSELING ONLINE DAN KOMPETENSI TEKNOLOGI INFORMASI DAN KOMUNIKASI GURU BIMBINGAN KONSELING - Neng Gustini; Tatang Ibrahim; Walid Ependi Pratama (Jurnal Isema : Islamic Educational Management, 2022)
The digital era as the impact of the science and technology revolution is a necessity that cannot be avoided by humans. In addition, the Covid-19 pandemic has caused learning to be diverted through online media. Not only subject teachers, but BK teachers also get the impact of technological developments and the covid-19 pandemic at the same time. This study aims to determine the relationship between cybercounseling management and the digital competence of guidance and counseling teachers at Madrasah Tsanawiyah, Ciamis Regency. This research is descriptive, the approach used is quantitative with the type of correlation. The technique of data collection is done by using a questionnaire technique (questionnaire). The data analysis technique was carried out in stages, starting from the validity test and the data reliability test. Then a statistical analysis was carried out consisting of a partial analysis per indicator and variable interpretation. Then the correlation analysis was carried out including the normality test of the data, the linearity test of the data, the correlation test, and the coefficient of determination test. From the results of data analysis, it was found that the Pearson correlation was 0.756. Based on the correlation coefficient interpretation table, 0.756 is in the interval 0.60 - 0.799, or is included in the strong category, it can be concluded that the relationship between cybercounseling management and the digital competence of BK teachers in MTs Kab. Ciamis has a strong relationship.